Persistent Amplification of DNA Damage Signal Involved in Replicative Senescence of Normal Human Diploid Fibroblasts. (18th September 2012) - Suzuki, Masatoshi; Suzuki, Keiji; Kodama, Seiji; Yamashita, Shunichi; Watanabe, Masami
Abstract : Foci of phosphorylated histone H2AX and ATM are the surrogate markers of DNA double strand breaks. We previously reported that the residual foci increased their size after irradiation, which amplifies DNA damage signals. Here, we addressed whether amplification of DNA damage signal is involved in replicative senescence of normal human diploid fibroblasts. Large phosphorylated H2AX foci (>1.5  μ m diameter) were specifically detected in presenescent cells. The frequency of cells with large foci was well correlated with that of cells positive for senescence-associated β -galactosidase staining. Hypoxic cell culture condition extended replicative life span of normal human fibroblast, and we found that the formation of large foci delayed in those cells. Our immuno-FISH analysis revealed that large foci partially localized at telomeres in senescent cells. Importantly, large foci of phosphorylated H2AX were always colocalized with phosphorylated ATM foci. Furthermore, Ser15-phosphorylated p53 showed colocalization with the large foci. Since the treatment of senescent cells with phosphoinositide 3-kinase inhibitor, wortmannin, suppressed p53 phosphorylation, it is suggested that amplification of DNA damage signaling sustains persistent activation of ATM-p53 pathway, which is essential for replicative senescence.